Measurement of Microvibration by Using Dual-Cavity Fiber Fabry-Perot Interferometer for Structural Health Monitoring - Dae-Hyun Kim; Jin-Hyuk Lee; Byung-Jun Ahn (Shock and Vibration)
Extensive researches have recently been performed to study structural integrity using structural vibration data measured by in-structure sensors. A fiber optic sensor is one of candidates for the in-structure sensors because it is low in cost, light in weight, small in size, resistant to EM interference, long in service life, and so forth. Especially, an interferometric fiber optic sensor is very useful to measure vibrations with high resolution and accuracy. In this paper, a dual-cavity fiber Fabry-Perot interferometer was proposed with a phase-compensating algorithm for measuring micro-vibration. The interferometer has structurally two arbitrary cavities; therefore the initial phase difference between two sinusoidal signals induced from the interferometer was also arbitrary. In order to do signal processing including an arc-tangent method, a random value of the initial phase difference is automatically adjusted to the exact 90 degrees in the phase-compensating algorithm part. For the verification of the performance of the interferometer, a simple vibration-test was performed to measure micro-vibration caused by piezoelectric transducer (PZT). As an experimental result, the interferometer attached on the PZT successfully measured the 50 Hz-vibration of which the absolute displacement oscillated between −424 nm and +424 nm.